Serial Port RS232 activated with on – line experiments in physics - Alizoti, Alion (Technium: Romanian Journal of Applied Sciences and Technology, 2026)
On – line experiments are being efficiently applied in physics, by influencing not only scientific research, but also other activities, such as engineering, or education. Therefore, devices, programs and curriculums are produced and developed to help relevant activities. Most computers use external ports and electromagnetic signals to communicate with outer devices, i.e. the serial port RS232. From this perspective, RS232 is conceived as the first powerful interface in a row to establish good connections between devices. Programs with basic or authoring languages are developed to control communications between computers and simple on – line experiments. Other computer ports, such as: USB ports, camera, microphone, headphones, etc. are also used to communicate experimental and physical data.